905 Inferior Mesenteric Artery Branch Aneurysm Causing Ischemic Colitis – A Sequela of Anabolic Steroid Use. (12th October 2021) - Joshi, S; Sebastian, M; Koshy, A
Abstract: An inferior mesenteric artery (IMA) aneurysm comprises less than 1% of all reported visceral artery aneurysms. A 34-year-old bodybuilder with a history of anabolic steroid (AS) use of unknown duration, dose and frequency initially presented to the hospital with recurrent bouts of acute onset abdominal pain and alternating episodes of watery-mucous diarrhoea and constipation. Patient's medical history was otherwise unremarkable with no stigmata of any connective tissue disorders. A diagnosis of ischemic colitis secondary to a distal IMA branch aneurysm measuring 6mm x 5mm x 10mm on CT was made three years after first presentation. Flexible sigmoidoscopy confirmed mucosal changes consistent with sigmoid ischemic colitis. A robotic anterior resection was performed due to two failed attempts at coiling the aneurysm. The histology was consistent with a secondary fibromuscular dysplasia in the IMA and its branches. There was a resolution of symptoms and return to normal stool and bowel function post-operatively. The commonest cause of an IMA aneurysm is the "jet disorder" phenomenon caused by incomplete atherosclerotic occlusion of the superior mesenteric (SMA) and celiac arteries (CA). While the link between AS use and dyslipidaemia is established, the patient's lipid profile was normal. We believe this case lends valuable insight into atypical causes of ischemic colitis and adds to the literature on AS use and vascular pathology.